Asymmetric chlorination of A2–A1–D–A1–A2 type non-fullerene acceptors for high-voltage organic photovoltaics. Issue 96 (15th November 2022) - Cong, Peiqing; Li, Xianda; Tang, Ailing; Wu, Jiang; Chen, Jianhua; Chen, Lie; Zhou, Erjun
Abstract : We synthesized the first asymmetric A2 –A1 –D–A1 –A2 type small molecule nonfullerene acceptor, HCl-BTA3, by chlorination on one side of the A1 unit, yielding a high open-circuit voltage of 1.20 V and a satisfactory power conversion efficiency of 11.2%. Abstract : Herein, we synthesized an asymmetric A2 –A1 –D–A1 –A2 type small molecule nonfullerene acceptor (NFA), HCl-BTA3, by chlorination on one side of A1 . The synergistic effect of the asymmetric structure and chlorination endows HCl-BTA3 with a large dipole moment, close molecular packing, and high-efficiency charge transfer and transport. After being blended with a carboxylate-based polymer donor, TTC-Cl, HCl-BTA3 achieved a high open-circuit voltage ( V OC ) of 1.20 V and a satisfactory power conversion efficiency (PCE) of 11.2%, which are among the highest values for high-voltage carboxylate-based polymers.